Polyaniline-Coated Electrospun Polyacrylonitrile Nanofibers for Effective Short-Chain PFAS (GenX) Removal from Water - Israt Jahan; Easmin Ara Tani; Harsh V. Patel; Renzun Zhao; Lifeng Zhang (Fibers)
A 6-carbon short-chain per- and polyfluoroalkyl substance (PFAS), GenX, also known as hexafluoropropylene oxide dimer acid (HFPO-DA) and its ammonium salt, has been manufactured in recent years as a replacement for perfluorooctanoic acid (PFOA), a traditional long-chain PFAS, due to the increasing environmental regulation of PFAS compounds in recent years. GenX has received significant attention because of the fact that it is more toxic than people originally thought, and it is now one of the six PFAS compounds that are placed under legally enforceable restrictions in drinking water, i.e., 10 ppt, by the United States Environmental Protection Agency (US EPA). In this research, we extended the use of polyacrylonitrile (PAN) nanofibers from electrospinning for GenX removal from water by coating them with polyaniline (PANI) through in situ polymerization. The obtained PANI-coated electrospun PAN nanofibrous adsorbent (PANI-ESPAN) demonstrated excellent GenX adsorption capability and could remove nearly all GenX (>98%) from a 100 ppb aqueous solution. This research provided valuable insights into short-chain PFAS remediation from water by designing and developing high-performance adsorbent materials.